Hephaestus Reloaded : Composed for Ten Hands / Efesto Reloaded: Composizioni per 10 mani - Antomarini, Brunella; Antomarini, Brunella; Traversa, Pietro; Camiller, Patrick; Burckhardt, Andreas; Maneta, Miltos; De Francesco, Alessandro; D'Amora, Vladimir; Berg, Adam (Book collections on Project MUSE., 2019)
Not simply as an object but rather as an immersive agency in which nature, knowledge, technique merge. The transcendence of the actual and the virtual into a "third" element is construed and analyzed in this book through conceptual schemes that rely on a post-binary or non-binary understanding of coincidences, triangulations, hybrids, or post-human combinatorics. What is ultimately explored is how transcendence is ejected from strictly theological, philosophical, or scientific groundings and emerges as a germinating point of becoming (something else).